Timmy's tent - Geatches, Hazel (United Kingdom : Aardman Animations limited, 2021)
Timmy and Harriet make a tent!
"Timmy's Tent" likely tells a simple story about Timmy from Timmy Time and his experience with a tent. The book probably focuses on basic vocabulary and concepts related to setting up or being inside a tent, aimed at beginner English readers. Location: 2A
Keywords: Timmy's tent book